(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article author analyzes the political and legal views of one of the greatest sons of the Kazakh nation, Mustafa Ozturk. Initially, the author gives an information about his life and history of Mustafa Ozturk return to his homeland. Referring to his interview published in various publications, as well as articles about him and memoirs the author analyzes his political and legal views. The author considering his views on language, religion, democratic values, freedom of speech, politics marks their importance and relationship with the present time. Especially the author considering separately his views and ideas about nationalism marks their importance today. The author also shares with own opinion about the reasons of his intervention in politics and talk openly own political and legal thoughts. Key words: politics, state, nationalism, elections.